Meningkatkan Hasil Belajar Matematika Materi Luas Bangun Ruang dengan Menggunakan Alat Peraga Sederhana Siswa Kelas V SD Negeri 2 Cakranegara - Apriana, Yuyun (Lembaga Yasin AlSys, 2022)
The objectives to be achieved in this research are: to find out the improvement of Mathematics Learning Outcomes in the Material of Spatial Building Areas Using Simple Teaching Aids for Fifth Grade Students of SD Negeri 2 Cakranegara in the 2021/2022 Academic Year. That the use of learning methods using simple teaching aids can improve the Mathematics results of Class V students of SD Negeri 2 Cakranegara. This is indicated by an increase in student learning outcomes in cycle I and cycle III with the final result of the study being the class average score before the action was 80.21 or classical completeness 60.71%, to 82.46 or classical completeness 71.53% in the first cycle, increased to an average of 84.79 or 82.14% in the second cycle and increased to an average of 90.14 or 100% in the third cycle. From the results of student observations showed that there was an increase in student activity which in the first cycle obtained a score of 19 or 67.86% to 21 or 75.00% in the second cycle and 25 or 89.29% in the third cycle. Increased student activities in learning Mathematics are supported by increased teacher activities in maintaining and improving the learning atmosphere using simple teaching aids, this can be seen from the observations of teacher activities where in the first cycle a score of 25 or 69.44% was obtained, to 27 or 75, 00% cycle II and increased to 32 or 88.89% cycle III.